Collection of airborne ultrafine cellulose nanocrystals by impinger with an efficiency mimicking deposition in the human respiratory system. Issue 2 (1st February 2019) - Roberts, Rose; Gettz, Kevin; Stebounova, Larissa V; Anne Shatkin, Jo; Peters, Thomas; Johan Foster, E.
Abstract: As cellulose nanocrystals (CNCs) are increasing in production, establishing safe workplace practices in industry will be paramount to their continued use and growth. Particles other than CNCs with similar high aspect ratios have exhibited toxicity on inhalation. Safeguards are needed to monitor concentrations of CNCs in air in industrial and laboratory settings to protect workers. However, because of their size, morphology, and chemical makeup, CNCs are difficult to characterize and differentiate from other dust and cellulose products. This work is focused on developing an effective method of characterizing the concentration of airborne ultrafine CNCs that may deposit in the respiratory tract. CNCs were tagged with rhodamine b (RhB-CNCs) for improved visualization and characterized using UV-vis spectroscopy (UV-vis), transmission electron microscopy (TEM), and dynamic light scattering (DLS), then aerosolized and collected via a novel method using plastic impingers. Concentration of RhB-CNCs was measured using UV-vis and scanning mobility particle sizer (SMPS). The plastic impinger with 3D-printed nozzle collected airborne CNCs at an efficiency that improves upon commercially available impingers for relevant particle sizes.